2015
DOI: 10.1111/all.12810
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17A increases TNF‐α‐induced COX‐2 protein stability and augments PGE2 secretion from airway smooth muscle cells: impact on β2‐adrenergic receptor desensitization

Abstract: As PGE2 is a multifunctional prostanoid with diverse roles in respiratory disease, our studies demonstrate a novel function for IL-17A in airway inflammation by showing for the first time that IL-17A impacts on the COX-2/PGE2 pathway, molecules known to contribute to disease exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Our further mediation analyses indicated that IL‐1β and TNF‐α, as two pro‐inflammatory cytokines, could play key roles in depressive symptom‐associated impaired BDR and neutrophilic airway inflammation. IL‐1β and TNF‐α were associated with decreased glucocorticoid expression along with impaired nuclear translocation, glucocorticoid receptor phosphorylation and β 2 ‐adrenergic desensitization . Therefore, these results suggest that depressive symptom‐associated activation of systemic M 1 macrophages could produce an over‐expression of pro‐inflammatory cytokines and promote T H 1 differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…Our further mediation analyses indicated that IL‐1β and TNF‐α, as two pro‐inflammatory cytokines, could play key roles in depressive symptom‐associated impaired BDR and neutrophilic airway inflammation. IL‐1β and TNF‐α were associated with decreased glucocorticoid expression along with impaired nuclear translocation, glucocorticoid receptor phosphorylation and β 2 ‐adrenergic desensitization . Therefore, these results suggest that depressive symptom‐associated activation of systemic M 1 macrophages could produce an over‐expression of pro‐inflammatory cytokines and promote T H 1 differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…As we have previously shown, PGE 2 induces heterologous desensitization of the β 2 -adrenergic receptor (Alkhouri et al, 2014;Rumzhum, Patel, et al, 2016, thus we hypothesized that EP 2 or EP 4 receptors may be involved in regulating β 2 -adrenergic receptor function in ASM cells. In accordance with our previous publication (Alkhouri et al, 2014), PGE 2 -induced tachyphylaxis to short-(salbutamol) or long-(formoterol) β 2 -agonists (measured by cAMP release).…”
Section: Pge 2 Does Not Induce Ep 2 or Ep 4 Receptor Mrna Expressionmentioning
confidence: 87%
“…The expression of COX-2 is induced at the site of inflammation in response to inflammatory stimuli, such as IL-1β, TNF-α, TGF-β 46,47 . Our results indicated that TGF-β1 NAb signficantly reduced COX-2 expression in HCT-116 cells exposed to the CMs of THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 99%